Modern geographic education in Ukraine - Oliynyk, Yaroslav; Nych, Tatyana (Journal of Education, Health and Sport, 2017)
One of the important directions of higher education in Ukraine is geographical. It involves education: junior bachelor; Bachelor's degree; Master's degree; Doctor of Philosophy; Doctor of sciences. A specialist with higher geographic education must possess a certain set of competencies that characterize him as a specialist and a person was indicated. The most important competences of graduates – geographers are social, economic, managerial, methodological and special, that allow flexibility to focus on graduate labor market was defined. The features of preparation of specialistsin geography, scientific and scientifically-pedagogical staff in higher educational establishments and scientific institutions in the following areas of knowledge: 1) natural sciences – directions of preparation: science of the earth (hydrology, meteorology, cartography); Geography (natural, economic); 2) sphere of service – direction of preparation – tourism; 3) architecture and construction – direction of preparation – geodesy and land management; 4) pedagogical education – direction of preparation – professional education (geography)were characterized.